A cholecystokinin B receptor antagonist and cocaine interaction, phase I study. (20th June 2018) - Elkashef, Ahmed; Brašić, James Robert; Cantelina, Louis R.; Kahn, Roberta; Chiang, Nora; Ye, Weiguo; Zhou, Yun; Mojsiak, Jurij; Warren, Kimberly R.; Crabb, Andrew; Hilton, John; Wong, Dean F.; et al.
Summary: Aims: RPR 102681, a cholecystokinin‐B antagonist, increased dopamine (DA) release and reduced cocaine self‐administration in animals. This pilot study sought to assess the safety and pharmacokinetics (PK) of co‐administration of RPR 102681 and cocaine, and to confirm the DA release mechanism of RPR 102681. Methods: Sixteen cocaine‐dependent participants were randomized to either placebo or RPR102681 at 3 ascending doses; cocaine was co‐administered at steady state of RPR 102681. [ 11 C]raclopride positron emission tomography scans were conducted at baseline and at each RPR102681 dose. Results: RPR 102681 was well tolerated, and safe to co‐administer with cocaine. RPR 102681 did not alter the PK of either cocaine or its metabolite benzoylecgonine and showed no intrinsic abuse liability. There was a trend toward reduction of cocaine craving scores. In contrast to animal studies, RPR 102681 significantly increased the binding potential of [ 11 C]raclopride in the ventral striatum ( t test, P  < .001) and caudate nucleus ( t test, P  < .0001) in a small subset of patients, suggesting that it may reduce intrasynaptic striatal DA. Conclusion: Overall, this pilot study suggests that RPR 102681 would be unlikely candidate, as an agonist medication for the treatment for cocaine addiction but worth investigating further for possible role in reducing craving.